Changes in the health status and functional outcomes in acute traumatic hand injury patients, during physical therapy treatment - Rebecca John; Chhaya V. Verma (Indian Journal of Plastic Surgery, 2011)
Introduction: Traumatic hand injury causes chronic disability. A large number of studies have reported impairments in clinical parameters, but few studies have described their disability experience. Aims To examine the functional disability and quality of life in traumatic hand injured patients receiving physical therapy. Settings and Design: The physiotherapy department in a multi-specialty public sector hospital. Convenient sampling method was used. Materials and Methods: The 36-item short-form health survey–MOS (SF-36, v2) and disabilities of arm, shoulder and hand (DASH) questionnaire were obtained and subjects were given physiotherapy, accordingly to their condition. Questionnaires were re-administered every month till discharge. Statistical Analysis Used: A One-way ANOVA test. Results: At end of 6 months, among eight subscales of SF-36, there is improvement in mean scores of physical functioning (39.1%). The bodily pain, general health, vitality, social function, and mental health had more than 100% improvement. DASH showed regression in disability (50.8%). Conclusions: Measuring quality of life (QOL) can provide detailed assessment of physical disability and treatment effects as well as the global impact of those effects on the person's daily life. Hence, the use of self-report questionnaires such as DASH and SF-36, combined with physical performance score, helps to achieve more comprehensive evaluation of outcome.